The impact of cultural change on the function of balu of Bidayuh-Bukar community in Kampung Taee, Serian - Jasica, Tatat; Nicholas, Gani (Sarawak Museums Department, 2024)
A significant feature of the Bidayuh community is the unique structure known as balu, which reflects the communal nature of their society. The balu serves various purposes. However, modernisation has led to alterations in both its functions and the materials used in its construction. This study aims to provide a thorough understanding of how social changes have influenced the changing functions of the balu, comparing its past significance to its current roles, as well as examining the implications of these changes for Bidayuh culture in the 21st century. The focus area for this research is Kampung Taee in Serian, Sarawak, where two specific balu structures – the Balu Gambang and the Balu Tuda - are located. Utilising a qualitative approach, the research involved semi-structured interviews and passive participant observation. The findings indicate that social or cultural changes in Kampung Taee have significantly affected the functions of the balu over time, and that its significance has decreased as many of its traditional uses have ceased to be practiced. Despite this decline, the study reveals a strong sentiment of cultural identity among the Bidayuh-Bukar community, as they continue to incorporate the balu into their modern lifestyles and traditional ceremonies, such as the Gawai Dayak celebration.